Regionally modulated radiomics analysis in PET/CT imaging: application to prognosis prediction of head and neck cancer - Yuan Sheng; Guoping Shan; Xue Bai; Binbing Wang; Yue Feng; Chong Xu; Yihao Li; Guoping Zuo; Hui Xu (Physical and Engineering Sciences in Medicine, 2026)

The dynamic mechanism of north-south tectonic disparities in the Rakhine Offshore Basin of Myanmar - Xuefeng Wang; Gui Fang; Hongping Wang; Guozhang Fan; Guoping Zuo; Xiaoyong Xu; Zhili Yang (Frontiers in Marine Science, 2025)
The Rakhine Offshore Basin is located within an accretionary wedge in the trench setting of an active continental margin, exhibiting complex and dynamic characteristics. Its structure is notably segmented from north to south and zoned from east to west. The basin is divided into two segments along the north-south axis: the northern segment features a compressional fold belt, while the southern segment is characterized by a strike-slip belt. Along the east-west axis, the basin is divided into two zones: the eastern zone represents the early-stage, steeply folded belt, where the shallow part is disrupted by thrust faults, while the western zone is marked by later, gentle sedimentary structure. Despite these detailed structural observations, current research on the structural and evolutionary characteristics of the Rakhine Offshore Basin is still limited, and the underlying causes of its north-south segmentation and east-west zonation remain unclear. Using seismic and drilling data, we provide a comprehensive examination of the structural and evolutionary characteristics of the basin. The results indicate that the Rakhine Offshore Basin formed at the end of the Upper Cretaceous, experiencing significant deformation from the end of the Upper Miocene to the Quaternary. The structural formation progressed from east to west, occurring earlier and more intensely in the east, and later and more gently in the west. After Miocene sedimentation, the regional structure underwent inversion, with the depocenter migrating from east to west. The segmentation from north to south and zonation from east to west in the Rakhine Offshore Basin are attributed to the oblique subduction and collision of the Indian Ocean plate with the Eurasian plate. The subduction angle is gentler in the south and steeper in the north, reflecting varying stress field mechanisms across these regions.

Detrital zircon provenance record of the northern shelf in the Rakhine Basin, Bay of Bengal - Liangbo Ding; Hongxia Ma; Guozhang Fan; Xiaoyong Xu; Hongping Wang; Guoping Zuo; Ying Zhang; Hui Sun; Jianan Wu; Junmin Jia; Ming Su; Ce Wang (Marine and Petroleum Geology, 2025)

Multi-proxy evidence of environmental change related to collapse of the Liangzhu Culture in the Yangtze Delta, China - Keyang He; Houyuan Lu; Guoping Sun; Xiang Ji; Yonglei Wang; Kaikai Yan; Xinxin Zuo; Jiangping Zhang; Bin Liu; Ningyuan Wang (Science China Earth Sciences, 2021)